Citizenship and civility in the university, a rapprochement of reading to the voices of the students at La Salle University, Colombia - Gloria Clemencia VALENCIA GONZÁLEZ; Lilia CAÑÓN FLÓREZ; Carlos Alberto MOLINA RODRÍGUEZ (Ediciones Universidad de Salamanca, 2016)
This article emerges from the Project «Higher education and civic education». In a rapprochement between conceptual topoi and affective citizenship exercises manifest in voices of students of Universidad de La Salle, interweave questions to the reading of citizenship and the civility. Voices reading dared to the epistemic; within qualitative collected concepts of citizenship and civility and analyzed by effective practices articulated with knowledge-own citizen and with the identification of relations with the state.